Epidemiologic study of eating disorders and related factors in Lima - Martínez, Patricia (2003)
The present study had the objectives of analyzing the prevalence of eating disorders in adolescent women attending school in Metropolitan Lima, identifying the factors related to those disorders and defining the population at risk of developing any of those disorders. A total of 2141 adolescents between 13 and 19 years old in their last three years of high school made up the probabilistic sample. This sample was chosen by clusters in two moments and stratified according to either prívate or public school. The Eating Behavior Inventory (ICA) was administered. Results showed that 16.4% of the cases had one or more eating disorders and 15.1% of the sample was at risk of developing one.